Prevalence of Castleman's disease in patients suffering from cervical lymphadenopathy. Issue 5 (17th August 2022) - Krokenberger, Michael; Schwamborn, Kristina; Strassen, Ulrich
Abstract: Objectives: To determine the prevalence of Castleman's disease (unicentric/idiopathic multicentric CD) in a retrospective cohort according to the newly defined international diagnostic criteria in patients, who underwent a lymph node removal at a tertiary care university hospital over a period of 10 years. Study design: Retrospective chart review. Material and methods: All Patients with cervical lymphadenopathy coded by ICD‐10‐CM with "I88.9, " "R59.0, " or "D47.Z2" between January 2010 and December 2020 and who underwent a lymph node extirpation were identified. In cases who met the diagnostic criteria for a potential unicentric or idiopathic multicentric CD (iMCD) diagnosis, the lymph node tissue was re‐evaluated by a pathologist. Results: A total of 714 patients with cervical lymphadenopathy were included into this single‐center retrospective study. After exclusion of patients with diseases that may mimic iMCD and cases for which material to perform histological re‐evaluation was lacking, a subset of 75 patients with "nonspecific lymphadenitis" or "reactive hyperplasia of lymph node" was identified, who underwent a renewed histopathological examination. One case fulfilled both the major and minor criteria of an iMCD diagnosis, and further 15 cases matched the histological criterion of an iMCD diagnosis (one of the two major diagnostic criteria), so that a UCD diagnosis according to the new criteria could be accepted. Conclusion: In this cohort, the subsequent application of the new diagnostic criteria led to further cases of CD (1.9% compared to 0.1% before) being recognized. Although incidence and prevalence of UCD and iMCD are low, clinicians should keep in mind this differential diagnosis as effective therapies are available. Level of Evidence: 4. Abstract : Castleman's disease is often first diagnosed in patients with cervical lymphadenopathy. The use of new diagnostic criteria will provide a simplified possibility of diagnosis, allowing the prevalence of the idiopathic multicentric as well as the unicentric form to be estimated